2004
DOI: 10.1128/jvi.78.2.1032-1038.2004
|View full text |Cite
|
Sign up to set email alerts
|

High Fidelity of Yellow Fever Virus RNA Polymerase

Abstract: Three consecutive plaque purifications of four chimeric yellow fever virus-dengue virus (ChimeriVax-DEN) vaccine candidates against dengue virus types 1 to 4 were performed. The genome of each candidate was sequenced by the consensus approach after plaque purification and additional passages in cell culture. Our data suggest that the nucleotide sequence error rate for SP6 RNA polymerase used in the in vitro transcription step to initiate virus replication was as high as 1.34 ؋ 10 ؊4 per copied nucleotide and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 36 publications
7
69
0
2
Order By: Relevance
“…These findings were corroborated by the observation that the MOD/DENV2 chimera replicated efficiently in Vero-B as well as in C6/36 cells (akin to the parent virus DENV2, but unlike MODV) ( (Pletnev et al, 1992;Pletnev & Men, 1998;Charlier et al, 2004). It was suggested that this may relate to as yet poorly understood incompatibilities within the artificially joined chimeric genomes, independent of changes in the virus entry pathways (Pugachev et al, 2004).…”
supporting
confidence: 70%
See 2 more Smart Citations
“…These findings were corroborated by the observation that the MOD/DENV2 chimera replicated efficiently in Vero-B as well as in C6/36 cells (akin to the parent virus DENV2, but unlike MODV) ( (Pletnev et al, 1992;Pletnev & Men, 1998;Charlier et al, 2004). It was suggested that this may relate to as yet poorly understood incompatibilities within the artificially joined chimeric genomes, independent of changes in the virus entry pathways (Pugachev et al, 2004).…”
supporting
confidence: 70%
“…2b) et al, 1992;Pletnev & Men, 1998;Charlier et al, 2004). It was suggested that this may relate to as yet poorly understood incompatibilities within the artificially joined chimeric genomes, independent of changes in the virus entry pathways (Pugachev et al, 2004).From the experiments described above, it appears that the block to productive MODV replication in insect cells (which should finally lead to release of infectious virus progeny) is not at the level of attachment and entry, but rather at a downstream post-entry stage of the virus life cycle. To study this hypothesis, Vero-B and C6/36 cells were transfected with 2 mg MODV RNA isolated from infectious particles (RNeasy Mini kit; Qiagen) using DMRIE-C Reagent (Invitrogen) according to the manufacturer's instructions.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…NS4B is a membrane-spanning, scaffolding protein which is known to mediate interactions with viral and cellular proteins on both sides of the endoplasmic reticulum membrane (5,15). It may be essential for nucleocapsid-envelope interaction during flavivirus assembly (23). A number of recombinant DEN4 viruses bearing putative Vero cell adaptation mutations were reported, indicating that NS4B protein is a key determinant in the adaptation of DEN4 virus to efficient replication in Vero cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…37 Despite the high-fidelity of YF17D virus RNA polymerase during viral RNA replication, the introduction of mutations can be detected. 38 Mutations noted at the structural protein level would be related to adaptation of the flavivirus envelope and prM-M protein to the YF17D capsid protein toward virus assembly. In addition, mutations observed elsewhere in the genome could be due to adaptation to growth in cell culture.…”
Section: Replacement Of Yf17d Structural Genes With Those Of Other Flmentioning
confidence: 99%